Average Achievable Rate Maximization for RIS-Assisted UAV Communication Systems - Yuandong Liu; Jianbo Ji; Juan Yang (IEEE Access)
Unmanned aerial vehicle (UAV) communication can effectively improve the quality of signal transmission in wireless communication due to its advantages of easy installation, high flexibility, and easy access to line-of-sight (LoS) links. However, in a complex communication environment, it is not easy to obtain the LoS link between the UAV and a ground user. As a promising technology, the reconfigurable intelligent surface (RIS) can provide a virtual LoS link to boost the communication quality when the LoS link is blocked. In the paper, we consider a RIS-assisted UAV communication systems which consist of a UAV and a RIS as well as a ground user. In order to maximize the average achievable rate of the ground user, this paper studies a design of joint RIS phase shift, UAV time slot power allocation and UAV trajectory in the considered systems. But the constructed joint optimization problem is a non-convex function, it is difficult to solve directly. We propose to divide the original problem into three sub-problems: power allocation optimization, phase shift optimization and UAV trajectory optimization, and propose an alternating iterative optimization algorithm to obtain a suboptimal solution. Compared with the other benchmark schemes, the algorithm we consider can significantly enhance the average achievable rate of ground user.